Experimental Investigation into Factors Influencing Methane Hydrate Formation and a Novel Method for Hydrate Formation in Porous Media - Wang, Yi; Li, Xiao-Sen; Xu, Wen-Yue; Li, Qing-Ping; Zhang, Yu; Li, Gang; Huang, Ning-Sheng; Feng, Jing-Chun (Energy & Fuels, 2013)
The behaviors of methane hydrate formation in porous media are investigated in three-dimensional vessels. The effects of the fugacity difference, the water-gas ratio, and the volume of the vessel on the formation rate of methane hydrate are studied. The results show that the formation rates are disproportionate to the fugacity differences but in proportion to the volume of the vessel and the change of the initial gas-water ratio has little effect on the rate of hydrate formation. Meanwhile, according to the discussion about the temperatures and resistances in hydrate reservoir, it is confirmed that methane hydrate forms from the boundaries to the center of the vessel. Furthermore, a new method is designed to form methane hydrate samples in porous sediments with high hydrate/water saturation and low gas saturation.